2021
DOI: 10.1111/ajsp.12491
|View full text |Cite
|
Sign up to set email alerts
|

Social unfairness as a predictor of social trust in China

Abstract: Exchange theory suggests that social unfairness, including conflict and inequality experienced locally at both personal and neighbourhood levels, reduces social trust generally. To test these uncharted suggestions, the present study analysed two‐wave panel survey data on a representative national sample of 25,618 Chinese adults. Results demonstrated that higher social unfairness experienced personally in 2010 significantly predicted lower social trust in 2014. Neighbourhood social unfairness, which was the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…(Cheung et al, 2022). Current research has shown that the perception of social fairness will affect trust,and individuals' perceptions of social fairness are signi cantly related to social trust[38][40][41][42] (Cheung et al, 2022; You, 2012; Sun et al, 2021; Li and He, 2022).…”
mentioning
confidence: 99%
“…(Cheung et al, 2022). Current research has shown that the perception of social fairness will affect trust,and individuals' perceptions of social fairness are signi cantly related to social trust[38][40][41][42] (Cheung et al, 2022; You, 2012; Sun et al, 2021; Li and He, 2022).…”
mentioning
confidence: 99%